Diseño de una mesa mecánica ajustable para el ensamble de núcleos en transformadores de Nacional de Transformadores TESLA (2023)
Nacional de Transformadores TESLA is a company dedicated to manufacturing voltage transformers. The assembly process of these transformers requires a mechanism to elevate the core to the level of the coil windows, thus facilitating the work of the operato.